Exercise Intolerance In Heart Failure With Preserved Ejection Fraction - Gupte, Anisha A. (Methodist Debakey Cardiovasc J, 2016)
More than 50% of Americans with heart failure have preserved ejection fraction (HFpEF). Exercise intolerance is a hallmark of HFpEF, but the pathophysiology is not well understood. Diverse etiologies and incomplete mechanistic understanding have resulted in ineffective management strategies to improve the outcomes of HFpEF. Traditional therapies that have been beneficial in the treatment of heart failure with reduced ejection fraction (HFrEF), neurohormonal blockade in particular, have not been effective in treating HFpEF. In this review, we address underlying mechanisms of HFpEF and present the rationale supporting exercise as a component of comprehensive management.